Power of integration - Calcagno, Alfredo Eric (2001)
Inquires what the position of Latin America and the Caribbean will be within the world order that will prevail in the 21st century and in which the USA will play a major role, albeit within a multipolar context. Opines that regional integration must be strengthened.